Introdução à arqueologia da escuta ou o nascimento do cinema sonoro a partir do espírito da ópera - Capeller, Ivan (2008)
An enquiry on the historical features of our ways of hearing, using Pierre Schaeffer's concept of objet sonore to reshape film sound's history through Michel Foucault's archaeological method.